Studi Kasus: Literasi Matematis Siswa Berdasarkan Gaya Belajar Kolb di SMPN 21 Surabaya - Anis Norawati (MATHEdunesa, 2020)
Mathematical literacy is an individual’s capacity to formulate, employ, and interpret mathematics in a variety of contexts. Mathematical literacy of each students can influenced by one internal factor, namely Kolb’s learning style. Kolb’s learning style consists of accomodating, diverging, assimilating, and converging. The research is a qualitative-descriptive reseacrh that aims to describe mathematical literacy students in PISA questioan solving on the content space and shape based on Kolb’s learning style. This research technique used questionnaire, test, and interview. The research subject were four students, each of had accomodating, diverging, assimilating, and converging learning style. The results of this research shows that (1) Students accmodating through the process of identifying important aspect of promblems, translating promblems into mathematical language, using mathematical cocepts and estimates to find solution, reinterpreting the result of calculations but not re-evaluating the solution. (2) Students diverging through the process of identifying important aspect of the problem, incorrectly translating problems into mathematical language, planning and implementing strategies using direct experiments, reinterpreting the result of calcualtions and not re-evaluating the solution. (3) Students assimilating through the process of identifying aspects of the problems, translating into mathematical language clearly, using mathematical consepts and writing step by step, reinterpreting the result of calculations, and re-evaluating the solution. (4) Student converging through the process of identying important aspect of the problems, not quite right in translating into mathematical language, using mathematical concepts and direct experiments to find solutions, reinterpreting the result and not re-evaluating the solution. Keywords: mathematical literacy, space and shape content, Kolb’s learning style